Quizizz Learning Media Development in Social Studies Subject - Wulandari, Fitria Irza; Suasti, Yurni; Ernawati, Ernawati (Postgraduate School, Universitas Negeri Padang, 2021)
The purpose of this research is to determine the feasibility of developing Quizizz learning media in social studies subjects at Tahfidz Madani Pasir Pengaraian Middle School. Besides that, this research will also produce learning media that have been tested for their feasibility level through validation by material experts, media expert validation, and validation learning experts and tested on 32 students in the school. This research is included in Research and Development (R&D) development research, namely research to develop learning media that will produce a product. The data analysis technique used is descriptive, which will be used to determine the feasibility of learning media. The data collected is in the form of quantitative and qualitative data; the instrument in this study is a Likert scale questionnaire; and the development design that will be carried out in this study is Analysis, Design, Development, Implementation, and Evaluation (ADDIE), which has five stages. Based on the results of media development, it was found that the results of the validation of material experts obtained an eligibility percentage of 85%, the eligibility percentage of media expert validation was 90%, validation from learning experts obtained an eligibility percentage of 82.8%, and finally, after being tested on students, a percentage of 90.18%. Based on the validation results of material and media experts, learning experts, and the results of trials on students, it can be concluded that Quizlet learning media is very suitable for use as social studies learning media.